Pelatihan Pembuatan Media BK Pencegahan Penyalahgunaan Narkoba Menggunakan Microsoft Power Point bagi Guru BK SMP/SMA di Kabupaten Ogan Ilir - Harlina, Harlina; Sofah, Rahmi; Putri, Rani Mega; Puriani, Risma Anita; Sucipto, Sigit Dwi; Anwar, Muhammad (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2017)
Basic competencies that teachers of Guidance and Counseling should have is the ability to use and to operationalize the Guidance and Counseling media. This capability is required because in her/his activities, a teachers of Guidance and Counseling should be able to design, to use, and to evaluate the effectiveness of the use of media in counseling and guidance services. Therefore it is required for the training of making Guidance and Counseling media to help teachers Guidance and Counseling in providing services to learners. Based on the results of the training of Guidance and Counseling media using Microsoft Power Point, 80% of teachers of Guidance and Counseling has been able to make a power point slide about preventing drug abuse through task independent. Through this training, teachers of Guidance and Counseling are expected to be more aware and understand that the needs of the times are getting changing and evolving, so that competence of technology and information should be improved also.